Combined Methodologies for Determining In Vitro Bioavailability of Drugs and Prediction of In Vivo Bioequivalence From Pharmaceutical Oral Formulations - De Simone, A.; Davani, L.; Montanari, S.; Tumiatti, V.; Avanessian, S.; Testi, F.; Andrisano, V. (Frontiers in Chemistry, 2021)
With the aim to develop an in vitro model for the bioavailability (BA) prediction of drugs, we focused on the study of levonorgestrel (LVN) released by a generic and a brand name 1.5 mg tablets. The developed method consisted in combing a standard dissolution test to an optimized parallel artificial membrane permeability assay (PAMPA) to gain insights on both drug release and gastro-intestinal absorption. Interestingly, the obtained results revealed that the tablet standard dissolution test, combined with an optimized PAMPA assay, highlighted a significant decrease in the release (15±0.01 μg min-1 versus 30±0.01 μg min-1) and absorption profiles (19±710-6±7cm/s Pe versus 41±1510-6 cm/s Pe) of LVN from a generic tablet when compared to brand name formulation, explaining unbalanced in vivo bioequivalence (BE). By using this new approach, we could determine the actual LVN drug concentration dissolved in the medium, which theoretically can permeate gastro-intestinal (GI) barrier. In fact, insoluble LVN/excipients aggregates were found in the dissolution media giving rise to non-superimposable dissolution profiles between generic versus brand name LVN tablets. Hence, the results obtained by combining dissolution test and PAMPA method provided important insights confirming that the combined methods can be useful in revealing crucial issues for the prediction of in vivo BE of drugs.